2021
DOI: 10.2147/copd.s313252
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis Identifies the Presence of Upregulated Ribosomal Housekeeping Genes in the Alveolar Macrophages of Patients with Smoking-Induced Chronic Obstructive Pulmonary Disease

Abstract: Background and Aims Alveolar macrophages (AM) play a crucial role in the development of chronic obstructive pulmonary disease (COPD). The role that AM plays in the molecular pathways and clinical phenotypes associated with tobacco-related emphysema remain poorly understood. Thus, we investigated the transcriptomic profile of AM in COPD patients with a history of smoking and explored the molecular mechanisms associated with enriched pathways and hub genes. Methods Four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For COVID-19-associated genes, we referred the PubChem ( https://pubchem.ncbi.nlm.nih.gov/#query=covid-19 ), CTD ( http://ctdbase.org/ ), DisGeNET ( https://www.disgenet.org/covid/diseases/summary/ ), baillielab net ( https://baillielab.net/maic/covid19 ) and KEGG DISEASE ( https://www.genome.jp/kegg/disease/ ) databases and data sets of ( Grant et al, 2021 ; Blanco-Melo et al, 2020 ; Mahmud et al, 2021 ; Singh et al, 2021 ; Overmyer et al, 2021 ; Mo et al, 2021 ). Regarding COPD-related genes, we considered DisGeNET ( https://www.disgenet.org/ ), CTD ( http://ctdbase.org/ ) and GeneCards ( https://www.genecards.org/ ) databases and data sets of ( O'Beirne et al, 2020 ; Han et al, 2021 ; Morrow et al, 2017 ; Hu et al, 2018 ; Raman et al, 2009 ; Huang et al, 2019 ; Morrow et al, 2019 ; Shen et al, 2021 ). These selected data sets above represent different clinical samples of COVID-19/COPD, specifically including alveolar lavage fluid, lung tissue, airway and peripheral blood.…”
Section: Methodsmentioning
confidence: 99%
“…For COVID-19-associated genes, we referred the PubChem ( https://pubchem.ncbi.nlm.nih.gov/#query=covid-19 ), CTD ( http://ctdbase.org/ ), DisGeNET ( https://www.disgenet.org/covid/diseases/summary/ ), baillielab net ( https://baillielab.net/maic/covid19 ) and KEGG DISEASE ( https://www.genome.jp/kegg/disease/ ) databases and data sets of ( Grant et al, 2021 ; Blanco-Melo et al, 2020 ; Mahmud et al, 2021 ; Singh et al, 2021 ; Overmyer et al, 2021 ; Mo et al, 2021 ). Regarding COPD-related genes, we considered DisGeNET ( https://www.disgenet.org/ ), CTD ( http://ctdbase.org/ ) and GeneCards ( https://www.genecards.org/ ) databases and data sets of ( O'Beirne et al, 2020 ; Han et al, 2021 ; Morrow et al, 2017 ; Hu et al, 2018 ; Raman et al, 2009 ; Huang et al, 2019 ; Morrow et al, 2019 ; Shen et al, 2021 ). These selected data sets above represent different clinical samples of COVID-19/COPD, specifically including alveolar lavage fluid, lung tissue, airway and peripheral blood.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, previous studies have shown that housekeeping genes can be involved in multicellular organogenesis, neurogenesis, developmental processes, and affected by disease. 104 - 113 Therefore, the identified plausible housekeeping genes among the UHEGs were not automatically ruled out as being involved in the development of hippocampal functions during the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for differential expression was set as adj.p.val < 0.05 and |logFC|> 0.585. After identifying differentially expressed genes, a volcano plot was generated, and expression distribution heatmaps between normal and disease groups were separately illustrated [ 21 23 ]. After identifying differentially expressed genes, a volcano plot was generated, and expression distribution heatmaps between normal and disease groups were separately illustrated.…”
Section: Methodsmentioning
confidence: 99%